2005
DOI: 10.1016/j.orthres.2005.04.005.1100230609
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of bone defect and enhancement of bone ingrowth using partially demineralized bone matrix and marrow stromal cells

Abstract: Purpose: This study aimed to investigate the capability of combining marrow stromal cells (MSC) and partially demineralized bone matrix (PDBM) to fill bone defect and enhance bone ingrowth using a canine non-weight-bearing gap model.Methods: Custom-made implants with 3 mm gap between the porous surface and the host bone were used. The implants were inserted into the distal femurs of 25 mongrel dogs and the gaps were randomly assigned to be filled with culture-expanded autologous MSC-loaded PDBM, autograft, fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Therefore, these progenitor cells may not have easy access to the ECM. Previous studies showed that the incorporation of MSCs into DBM implants improved the quantity and quality of bone formed in humans and canine models 27–29. Since we sought to examine the osteoinductivity of the in vitro generated ECM alone, the inclusion of osteogenic cells was not considered for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these progenitor cells may not have easy access to the ECM. Previous studies showed that the incorporation of MSCs into DBM implants improved the quantity and quality of bone formed in humans and canine models 27–29. Since we sought to examine the osteoinductivity of the in vitro generated ECM alone, the inclusion of osteogenic cells was not considered for this study.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Notable differences in MSCs have been observed during culture expansion of MSCs including the presence of chromosomal abnormalities, which lead to tumorigenicity concerns. 4,7,25 Also, ex vivo expansion methods are typically utilized to increase the number of bone contributing cells from tissue sources that have sub-efficacious amounts of MSCs (e.g. bone marrow).…”
Section: Discussionmentioning
confidence: 99%
“…Shih et al . () investigated the effect of DBM on implant fixation in a canine non‐weight‐bearing gap model, and showed a significantly better effect of DBM compared to allograft. However, the DBM used was mixed with mesenchymal stem cells, which are expected to provide osteogenic capacity to DBM.…”
Section: Discussionmentioning
confidence: 99%
“…Its application has focused on spine fusion, fractures and as an extender to other grafting materials in repairing cysts and well‐supported skeletal defects (Lane, ). Regarding implant fixation within revision arthroplasty, only a few clinical trials and animal studies have been published (Cook et al ., ; Shih et al ., ).…”
Section: Introductionmentioning
confidence: 97%